KONTRIBUSI PAJAK SARANG BURUNG WALET TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN BANGKA INDUK - SILVY CHRISTINA (Media Bisnis, 2013)
This research was conducted at Kantor Dinas Pendapatan, Pengelolaan Keuangan dan Aset Daerah of Bangka Induk Regency. The research was based on the bird’s nest tax in comparison to domestic income of Bangka Induk Regency. The research methodology used the comparison of the target to the realization of revenue frombird’s nest tax and the contribution analysis of bird’s nest tax in comparison to domestic income of Bangka Induk Regency. In 2009 and 2010, the real collection from bird’s nest tax did not reach the target.In 2011, the revenue reached the target. The contribution amount of bird’s nest tax in comparison to the domestic income was 0.28% in 2009, 0.36% in 2010, and 0.30% in 2011. The average contribution from 2009 to 2011 was only 0.31%. It could be concluded that the bird’s nest tax could be higher in 2012 due to the tax intensification and extensification to raise the domestic income.